Cyclical consumption - Tino Berger; Lorenzo Pozzi (Tinbergen Institute, 2023)
Recessions and expansions are often caused or reinforced by developments in private consumption - the largest component of aggregate demand - which, as a result, varies over the business cycle. As such, an accurate measurement of the cyclical component of consumption and an understanding of its drivers is essential. We estimate US cyclical consumption using a multivariate Beveridge-Nelson decomposition based on a medium-scale Bayesian vector autoregression. The choice of variables included in the analysis is informed by a general savers-spenders model. We compare the predictive power of our multivariate cyclical consumption variable to that of univariate measures such as the recently introduced cc variable by Atanasov et al. (2020). An informational decomposition points to variables related to incomplete markets (precautionary motives and credit constraints) as the main contributors to cyclical consumption. This is confirmed by a causal analysis that attributes between 20% and 40% of cyclical movements in consumption to uncertainty shocks.
Keywords: E21; E32; C32; 330; cyclical consumption; Beveridge-Nelson decomposition; multivariate information; incomplete markets; uncertainty shocks